Beliefs of Bangsamoro Madaris learners about language learning and their relationship with academic performance - Abdullah Karim, Kurais; Abd.Samad, Arshad; Elias, Habibah (2008)
This study investigated the beliefs about language learning of 100 Bangsamoro Madaris English learners in Southern Philippines. The survey instrument, ‘Beliefs About Language Learning Inventory’ or BALLI (Horwitz 1987) which included 34 items on a Likert-type scale, was used to collect data on the learners’ beliefs. The aims of the study were to describe the beliefs of the respondents about language learning and to explore the relationship between beliefs and academic performance in order to provide empirical backing of the relationship, otherwise lacking in beliefs literature (Peacock, 1999). The findings of the descriptive analysis indicate several firmly held beliefs among the respondents including those that have important teaching implications. Pearson Product Moment correlation analysis between beliefs and the final scores in the English subject indicates relationship in five belief items, two of which are different from previous studies (Peacock, 1999), lending support to the context specificity of beliefs.